PENGARUH MODEL PROBLEM BASED LEARNING MENGGUNAKAN METODE TALKING STICK TERHADAP HASIL BELAJAR PKN KELAS IV DI SDN 1 ASTANA - Noviyanti, Indah; Sari, Diana; Nurkholis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to investigate the influence of the Problem Based Learning (PBL) model using the Talking Stick method on the learning outcomes of fourth-grade students in Civic Education (PKn) at SDN 1 Astana. The background of this study is based on the low learning outcomes and lack of student activity in Civic Education lessons, which are often dominated by conventional teaching methods. This quantitative study employed a quasi-experimental design with a pretest-posttest control group. The sample consisted of two classes selected through purposive sampling, with the experimental class receiving PBL with the Talking Stick method and the control class receiving conventional learning. Data collection techniques included tests, observation, and documentation, while data analysis used the independent sample t-test. The results showed that the experimental class achieved a higher posttest average score than the control class, indicating a significant improvement in students' cognitive abilities. Furthermore, student activity and participation also increased in the experimental class. These findings suggest that the implementation of the PBL model combined with the Talking Stick method can effectively improve students' learning outcomes and foster active participation in Civic Education learning.